EFFECTS OF BLUE LIGHT EXPOSURE ON RAPID EYE MOVEMENT SLEEP DURATION AND MELATONIN LEVELS IN CHILDREN: A COMPREHENSIVE LITERATURE REVIEW - Natalia Krajewska,; Rafał Bednarczyk,; Natalia Bednarczyk,; Radosław Krzysztof Binkowski,; Agnieszka Kurek,; Aleksandra Lejman,; Aleksandra Mazurkiewicz,; Hubert Sidor,; Monika Wołosik,; Szymon Zysiak, (International Journal of Innovative Technologies in Social Science, 2026)
Blue light exposure from electronic devices has emerged as a significant environmental factor affecting children's sleep architecture and circadian physiology. This comprehensive literature review synthesizes empirical evidence from 2020-2025 examining the effects of blue light exposure on rapid eye movement (REM) sleep duration and melatonin levels in pediatric populations. A systematic search of PubMed, Web of Science, and related databases identified studies employing objective measurement methods, including polysomnography (PSG) and actigraphy validated against PSG, with melatonin measurement via salivary DLMO. The current evidence demonstrates that blue light exposure, particularly from electronic devices in the evening hours, significantly suppresses melatonin production in children even at very low illuminance levels (5-40 lux), producing melatonin suppression of 70-99% depending on light intensity and spectral composition. Blue light predominantly affects melatonin suppression and REM sleep through intrinsically photosensitive retinal ganglion cells (ipRGCs) expressing melanopsin with peak sensitivity at approximately 480 nm. Studies indicate that evening blue light exposure reduces REM sleep duration, increases REM fragmentation with elevated microarousals, increases sleep onset latency, and impairs sleep efficiency in children. The magnitude of effects on REM sleep and melatonin suppression demonstrates circadian timing dependency, with exposure during 21:00-22:30 hours producing maximum sleep disruption. Evening screen use, particularly interactive forms, is associated with delayed sleep onset and reduced total sleep duration in children measured via objective actigraphy. Interventions restricting blue light exposure before bedtime through screen abstinence and blue light-blocking glasses show slight improvements in sleep timing and circadian phase advancement. This review concludes that evidence-based guidelines recommending screen restriction in the 1-2 hours before bedtime are justified based on documented physiological mechanisms and objective sleep disruption in children.